Understanding Consumer Satisfaction through Price Perception, Product Quality, and the Mediating Role of Promotion - Chairiel Oktaviar; Harefan Arief; Eko Tama Putra Saratian; Eri Marlapa (Journal of Fundamental Management (JFM), 2026)
This research examines the influence of price perception, product quality, and promotion on consumer satisfaction with Mixue. Primary data were obtained via questionnaires from 189 consumers in Kota Tangerang who had purchased Mixue beverages on at least one occasion, and analyzed using partial least squares (PLS) regression. The findings reveal that while price perception, product quality and promotion have positive significant effect on cutomer satisfaction also price perception and product quality have positive significant effect on promotion. Collectively, the mediation results confirm that promotion functions as a significant intervening variable in both pathways. Notably, in the case of price perception, promotion fully mediates the relationship, whereas in the case of product quality, promotion partially mediates the relationship.